Strategi Pemasaran dan Upaya Menarik Minat Nasabah Pada Produk Tabungan Emas di PT. Pegadaian Syariah Unit Sadabuan Padangsidimpuan - Sarmiana Batubara; Afrini Nasution (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
Based on data on the number of gold savings customers per year. Has fluctuated from 2016-2019, in 2017 it descreased by 28,02 percent. In 2018 it descreased by 50,14 percent. However in 2019 it experienced an increase of 74,53 percent. The formulation of the problem is how the marketing strategy of PT. Pegadaian’s sharia branch gold savings product alternating funds whether PT. Pegadaian’s sharia branch back and forth is in accordance with the 7p marketing theory. The purpose of this study was to determine the marketing strategy of PT. Pegadaian’s sharia alaman branch of gold savings products. And to find out the marketing strategy for gold savings products is in accordance with the 7p marketing mix. The teory used in this research is the teory of interest, strategy, marketing, marketing strategy, marketing mix and gold saving teory. This research is descriptive qualitative with data colecction techniques using interviws, observation and documentation. While the data sources used are primary data and secondary data. From the results of this study it can be cocluded that the marketing strategy is with 7p. Product, Price, Place, Promotion, People, Process, Physical Evidence. The marketing strategy of PT. Pegadaian Sharia branches in the back and froth is in accordance with the 7p marketing mix. It can be seen that in 2019 it has increased, which in dealing with the decrease in the number of pawnshop customers makes a policy that is for all costumers, be the pawn customers, arrum haji costumers or other customers obliged to open a gold savings .